PTCL, NOS: An update on classification, risk-stratification, and treatment - Weiss, Jonathan; Reneau, John; Wilcox, Ryan A. (Frontiers in Oncology, 2023)
The peripheral T-cell lymphomas (PTCL) are relatively rare, heterogeneous, and therapeutically challenging. While significant therapeutic gains and improved understanding of disease pathogenesis have been realized for selected PTCL subtypes, the most common PTCL in North America remains “not otherwise specified (NOS)” and is an unmet need. However, improved understanding of the genetic landscape and ontogeny for the PTCL subtypes currently classified as PTCL, NOS have been realized, and have significant therapeutic implications, which will be reviewed here.